Biomechanical analysis of badminton different forward steps - Lin, H.-W.; Huang, K.-S.; Pan, K.-M.; Tsai, C.L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to compare the biomechanical variables between 2-step and 3-step forward steps in badminton. Eight collegiate elite male badminton players participated in this study. Eight Vicon T-20 cameras (300 Hz) were used to record the 3D kinematics data and a Kistler force plate (1500 Hz) was used to collect the GRF data of the last steps. A Wilcoxon matched-pairs signed-rank nonparametric statistical test was conducted to compare the differences between two kinds of forward step movements. The results showed that the movement time for 3-step movement was significantly faster than 2-step. We recommend that the badminton players should practice 3-step forward footwork technique. The additional strength and power training for lower limbs should be carried out for the footwork training.